Glucose starvation induced autophagt is A potent apopotic cell death mechanism in multidrug resistant HL60/ADR cells - Abdel-Shakor, A-B. M. (2010)
Multidrug resistance in cancer is significantly limits the effectiveness of cancer chemotherapy. The main pupose of the present study is to investigate the role of autophagy induced by glucose starvation in apoptosis induction in multidrug resistant human leukaemia HL60/ADR cell line. The present data indicates that glucose starvation induced autophagy as determined by the level of LC3 protein (autophagy marker), whereas serum deprivation did not induce autophagy at the same time points.
Includes references.
Summary in Arabic.
Keywords: Multidrug Resistance-Associated Proteins; Ceramides; Cancer -- Chemotherapy; Glucose -- Therapeutic use; Glucose -- Metabolism; Sphingomyelin -- Analysis; Autophagy; Apoptosis -- Therapeutic use; Apoptosis -- Research